Microplastics and nanoplastics in the air: a review - Bui, Van Nang; Dung, Nghiem Trung; Nguyen, Thi Thu hien (Vietnam Journal of Science and Technology, 2025)
Given the increasing concern about microplastics (MPs) and nanoplastics (NPs) in the atmosphere, numerous studies have been conducted on their presence and impacts. This review explores the occurrence, sources, physicochemical characteristics, and the sampling and analytical methods of MPs and NPs in ambient air. MPs are primarily found in the form of fibers and fragments, with sizes generally exceeding several micrometers, and have been detected in various environments, including urban, industrial, coastal, and remote areas. Currently, there are no standardized methods for sampling and analyzing MPs and NPs in the atmosphere. Existing studies predominantly employ passive sampling methods to collect depositable microplastics and active sampling methods for suspended MPs. In the laboratory, most samples are treated with H2O2 and then separated by density before being analyzed using microscopy and spectroscopic techniques such as FT-IR and Raman. However, the current sampling and analytical methods have proven insufficient for detecting the presence of NPs in the air. Therefore, there is a need to develop new sampling and analytical methods to determine them in the atmospheric environment.